FDI in Selected Developing Countries: Evidence from Bundling and Unbundling Governance - Simplice Asongu (European Journal of Government and Economics (EJGE), 2019)
The objective of this study is to assess governance drivers of FDI in a panel of BRICS and MINT countries for the period 2001-2011.~ We bundle and unbundle governance determinants using a battery of contemporary and non-contemporary estimation techniques. Our findings reveal the following: Firstly, for both contemporary and non-contemporary specifications, while the majority of our governance determinants of Gross FDI are significant, they are overwhelmingly insignificant for Net FDI. Secondly, the significance of the governance dynamics in increasing order of magnitude are general governance, political governance, economic governance, political stability, regulation quality and government effectiveness. Thirdly, for non-contemporary specifications, the significance of governance variables is as follows in ascending order of magnitude: economic governance, institutional governance, general governance, corruption-control, political governance and political stability. The importance of combining governance indicators is captured by the effects of political governance, economic governance and institutional governance. The results indicate that the simultaneous implementation of the various components of governance clarifies a country's attractiveness for FDI location. Policy implications are discussed with particular emphasis on the timing of FDI and its targeting.
Keywords: C52; F21; F23; P37; P39; 330; foreign direct investment; emerging countries; governance